Assessment of the Impact of Factors Determining the Teachers’ Salary: the Case of Radviliškis District - Matuzevičiūtė-Balčiūnienė, Kristina; Jašinskienė, Dovilė (Socialiniai tyrimai, 2021)
Based on the results of the theoretical analysis, problems such as the aging population of teachers, the lack of attractiveness of the teaching profession and the shortage of teachers in certain subjects have been identified in the education system, as well as in some geographical areas. The recent reform of the teacher’s payment system in Lithuania was started in 2018, so the problem analysed in the article is relatively new, which leads to a lack of research, as apart from some statistics, analysts’ insights and forecasts, scientific research on this topic is insufficient. In this study, an independently pooled cross-sections model is used to assess the factors of teachers ’salaries. The results of the research show that after the introduction of the full- time payment system, the salaries of teachers in Radviliškis district did not increase. This was due to the reduction in the size of the workload following the introduction of the full- time payment system.
Keywords: education policy; education reform; teacher; full-time; teacher’s salary